(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2014)
To find out the clinical profiles of peripartum neurodeficit, a prospective observational study in 23 patients was conducted from 1st July 2008 to 31st June 2009 in the department of Physical Medicine, Chittagong Medical College. Presenting neurological findings and FIM scores for self-care, sphincter control, transfer and locomotion were measured. Ambulation of the patients was paretic and dependent. Paralysed body parts were mainly both lower limbs (69.6%). Disability pattern was mainly in walking (82.6%). Reflexes of most of the patients and mostly lower limbs were affected. Muscle power was reduced in the lower limbs in 100% and in the upper limbs in 40% of the patients. Neurological profiles are measured with functional independence measure (FIM) scale. Normal FIM scores are of self-care-42, sphincter control-14, transfer-21 and locomotion-14 and combined score is 91. In the observed patients, FIM scores of selfcare were; minimum 9 to maximum 21, sphincter control 2 to 5, transfer 3 to 9, locomotion 2 to 5. Combined total FIM score was found minimum 16 to maximum 49 and mean 36.70 + 11.60 out of normal score 91. From this study it may be concluded that peripartum neurodeficit may cause various neurological disabilities. JCMCTA 2014 ; 25 (1): 18-21